THE RELATIONSHIP BETWEEN ARM MUSCLE STRENGTH AND WRIST FLEXIBILITY WITH FOREHAND SHOT ACCURACY IN TABLE TENNIS GAMES FOR STUDENTS AT STATE JUNIOR HIGH SCHOOL 2 PULAU RIMAU BANYUASIN - I Bagus Endrawan; Aprizal Fikri; Zusyah Porja Daryanto; Riyan Jaya Sumantri (Jurnal Pendidikan Olah Raga, 2024)
The aim of this study was to determine the relationship between arm muscle strength and wrist flexibility and the accuracy of table tennis forehand smashes. Using the correlational method, the sample consisted of 30 male students who took part in extracurricular activities. The data analysis used is simple correlation analysis for each independent variable with the dependent variable, while for them together it is double correlation. The results of the research between variables X1 and Y obtained rcount = 0.892 > rtable = 0.361 then H0 was rejected and Ha was accepted, variables = 0.892 > rtable = 0.361 then H0 is rejected and Ha is accepted and the value of Fcount = 52.400 > Ftable = 3.35 means H0 is rejected and Ha is accepted. Because the three variables show a positive direction, it can be concluded that there is a relationship between arm muscle strength and wrist flexibility and the accuracy of forehand strokes in table tennis for students at State Junior High School 2 on Pulau Rimau, Banyuasin.